Pathomorphological features of the structure of the uterus of fetuses from mothers with pregnancy complicated by pre-eclampsia of varying degrees of severity - V. D. Markowski; L. S. Kupriyanova (Zaporozhye State Medical University, 2014)
Aim. In order to determine the effect of preeclampsia (PE) of the mother on the structural pecularities of uterus of fetuses the structure of the uterus of 41 antenatally dead fetuses was studied using organometric, histologic, histochemical, morphometric and statistical methods. Methods and results. It has been established that the maximum decrease of indices of mass and length of the uterus is in fetuses of mothers with medium degree of PE and severe PE, the minimum - in fetuses of mothers with mild PE. Unidirectional changes were found in the calculation of indicators of the wall thickness of the uterus and its structural components. Histological structure of the uterus of fetuses from mothers with PE is characterized by proliferation of the glandular epithelium; growth of coarse fibrous connective tissue in the mucous membranes and muscle layers; dystrophic and necrotic changes in the vascular endothelium. Conclusion. Identified features can manifest themselves in reproductive dysfunction in the future ontogenesis.